Museums of geological and mining heritage. Case study for El Suspiro mine (Cúcuta, Colombia) (2021)
This work provides information on several existing museums in the region of Cúcuta (Colombia), which have elements that can be considered geological or mining heritage. These museums could be integrated into the creation of a mining theme park in conjunction with the closure of the El Suspiro limestone mine. The objective of this study, in addition to disseminating the information, is to show the existing museums at the municipalities of Los Patios and Cúcuta, where there are collections of fossils, minerals and archaeological elements found in the region. Additionally, there are enginery and elements that were used for mining development in the region as well as in the School of Mining Engineering at the Universidad Francisco de Paula Santander (UFPS). The methodology of this study involved an analysis of the topic at global, national and local contexts, visits to the museums and the mine site, as well as photographic records and geo-positioning. It is concluded that it is feasible to implement geotouristic visits at the El Suspiro limestone mine, as well as visits to the existing museums in Agualinda and Vados counties, and the museum of geological and mining heritage of the Universidad Francisco de Paula Santander at Cúcuta, Colombia.